Study of the Thickness of Curtain Grouting Ring for the life-cycle of Tunnel in Water-rich Fault Fracture Zone. Issue 1 (March 2020) - Jia, Yanling; Lu, Ouyang; Zhou, Shaowen; Wang, Gang
Abstract: Junchang Tunnel passes through fault fracture zone where joints and fracture developed, the water-rich zone is wide and the geological condition is extremely complex, which is likely to induce the water gushing and mud gushing. Based on the project, the proper thickness of curtain grouting ring for the life-cycle of tunnel in water-rich fault fracture zone is analyzed, and the main conclusions are as follows: (1) Comprehensive advance geological forecast including ultra-high density resistance method, land sonar method, transient electromagnetic method and drilling method are adopted to achieve good prediction results in the fault fracture zone of DK7+812 to DK7+862; (2) The full-face curtain grouting method can effectively reduce the formation deformation caused by tunnel excavation in the tunnel construction in water-rich fault fracture zone, and the effect of water plugging is great; (3) According to the formula of thick wall tube, the experience of grouting and water plugging in existing tunnels, and the comparison of finite element method, the thickness of curtain grouting ring should be greater than 5m to meet the safety requirements. Considering the safety requirements and the reduction of curtain grouting ring in the operation period, the thickness of curtain grouting ring needs to be increased to 7m.